2004
DOI: 10.1002/humu.20088
|View full text |Cite
|
Sign up to set email alerts
|

Sequence variations of the ?-globin genes: Scanning of high CG content genes with DHPLC and DG-DGGE

Abstract: The alpha-globin chains are encoded by two duplicated genes (HBA2 and HBA1, 5'-3') showing overall sequence homology >96% and average CG content >60%. alpha-Thalassemia, the most prevalent worldwide autosomal recessive disorder, is a hereditary anemia caused by sequence variations of these genes in about 25% of carriers. We evaluated the overall sensitivity and suitability of DHPLC and DG-DGGE in scanning both the alpha-globin genes by carrying out a retrospective analysis of 19 variant alleles in 29 genotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…Previous reports have shown that DGGE run at optimised conditions can be a highly sensitive tool for such fragments [Hayes et al, 1999;Lacerra et al, 2004;Wu et al, 1999], and is therefore an appropriate platform for assessing new methods for this application. One report, which discusses HRM curve analysis of GC-rich fragments [Reed and Wittwer, 2004], suggests that GC content has no effect on HRM curve analysis, and also that biphasic melting curves may be easier to analyze than those with a single melt domain.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that DGGE run at optimised conditions can be a highly sensitive tool for such fragments [Hayes et al, 1999;Lacerra et al, 2004;Wu et al, 1999], and is therefore an appropriate platform for assessing new methods for this application. One report, which discusses HRM curve analysis of GC-rich fragments [Reed and Wittwer, 2004], suggests that GC content has no effect on HRM curve analysis, and also that biphasic melting curves may be easier to analyze than those with a single melt domain.…”
Section: Discussionmentioning
confidence: 99%
“…On this basis, no functional consequences of the p.Ala27Thr substitution can be predicted according to known site mutation determinants (Storz and Moriyama 2008;Weber and Campbell 2011). The same amino acid replacement at the same position has already been detected in α-chain globin variants from goat breeds present in southern Italy (Puglia and Sardegna) (Pieragostini et al 2005;Pirastru et al 2009) and from human families in Caserta (Campania) (Lacerra et al 2004). Either in Agerolese bovine, Apulian/Sardinian goat, and human Casertian α-globin variants, this substitution involves a CpG dinucleotide that is considered as a mutation hotspot (Perutz 1990).…”
Section: Resultsmentioning
confidence: 86%
“…In general, DHPLC is a rapid and cost-effective method because no particular manipulations or reagents are required pre-or post-PCR amplification. However, existing DHPLC mutation screening protocols available for b-globin gene are based on the Transgenomic Wave TM analyzer [8,9], requiring a significant capital injection, which can be particularly problematic for small laboratories. The DHPLC methodology described herein allows its implementation in every laboratory in possession of a HPLC instrumentation, since only the purchase of the separation column is required and the resulting chromatograms are generated equally fast as with the Transgenomic setup.…”
Section: Resultsmentioning
confidence: 99%
“…Denaturing high-performance liquid chromatography (DHPLC) is a cost-effective methodology that has been successfully applied for mutational detection of several genes [7], including the a-and b-globin genes [6,8,9], approaching 90-100% in sensitivity and specificity. However, the earlier-mentioned protocols are based on the Transgenomic Wave TM DHPLC system, which is expensive and therefore poses a hurdle for its implementation in low-budget laboratories, particularly those in developing countries.…”
Section: Introductionmentioning
confidence: 99%